What we can learn about strategies, language learning, and life from two extreme cases: The role of well-being theory - Oxford, Rebecca L. (Studies in Second Language Learning and Teaching, 2014)
This article presents two foreign or second language (L2) learner histories representing the extreme ends of the spectrum of learner well-being. One story reflects the very positive learning experiences of a highly strategic learner, while the other story focuses on a less strategic learner’s negative, long-lasting responses to a single traumatic episode. The theoretical framework comes from the concept of well-being in positive psychology (with significant adaptations). In addition to contrasting the two cases through the grounded theory approach, the study suggests that the adapted well-being framework is useful for understanding L2 learning experiences, even when the experiences are negative.